2015
DOI: 10.1186/s12985-015-0424-z
|View full text |Cite
|
Sign up to set email alerts
|

Duck enteritis virus UL54 is an IE protein primarily located in the nucleus

Abstract: BackgroundThe UL54 protein of Duck Enteritis Virus (DEV) is a homolog of herpes simplex virus-1 (HSV-1) immediate-early infectious cell protein 27 (ICP27), a multifunctional protein essential for viral infection. Nonetheless, there is little information on the UL54 protein of DEV.MethodsThe UL54 gene was cloned into the pPAL7 vector, and the recombinant protein, expressed in the E. coli Rosetta, was used to produce a specific antibody. Using this antibody, Western blotting and indirect immunofluorescence analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Researchers have prepared oil emulsified inactivated vaccine against Salmonella Typhimurium (ST), DP and Duck Hepatitis Virus (DHV) which was found safe, potent and capable of protecting ducklings against ST, DP and DHV infections effectively (Hanan et al 2014;. Researchers are investigating the role of UL16 and UL54 genes also and their expressed proteins from DEV, so that they can also be utilized in planning prophylactic strategy against DEV virus in susceptible bird populations (He et al 2012;Liu et al 2015;Liu, Cheng, et al 2016). A DEV-vectored vaccine containing a recombinant DEV (rDEV-ΔUL2-HA) inserted with the HA gene from duck-origin H9 subtype (H9N2) AIV into the UL2 gene by homologous recombination has been developed recently.…”
Section: Vaccinationmentioning
confidence: 99%
“…Researchers have prepared oil emulsified inactivated vaccine against Salmonella Typhimurium (ST), DP and Duck Hepatitis Virus (DHV) which was found safe, potent and capable of protecting ducklings against ST, DP and DHV infections effectively (Hanan et al 2014;. Researchers are investigating the role of UL16 and UL54 genes also and their expressed proteins from DEV, so that they can also be utilized in planning prophylactic strategy against DEV virus in susceptible bird populations (He et al 2012;Liu et al 2015;Liu, Cheng, et al 2016). A DEV-vectored vaccine containing a recombinant DEV (rDEV-ΔUL2-HA) inserted with the HA gene from duck-origin H9 subtype (H9N2) AIV into the UL2 gene by homologous recombination has been developed recently.…”
Section: Vaccinationmentioning
confidence: 99%
“…IE genes are expressed in the presence of CHX although the transcription of E and L genes is suppressed [31]. We also treated DEV-infected cells with GCV and examined UL54 (an IE gene) [32], US2 (an L gene) [33], UL13 (an E gene) [34], and β-actin as controls. We found that UL21 gene expression was inhibited in the groups treated with GCV and CHX.…”
Section: Discussionmentioning
confidence: 99%
“…The reactivity of the antibody was determined using western blot analysis [ 18 ]. On the one hand, the lysates of bacteria transformed with pET-32a(+) vs. pET-32a(+)/US10 were blotted to test the cross-reactivity of anti-US10 serum.…”
Section: Methodsmentioning
confidence: 99%
“…IFA was conducted using a standard procedure [ 18 ]. Briefly, DEV-infected cells were harvested at 12, 24, 36, and 48 h post-infection, plated onto coverslips, and fixed with 4% paraformaldehyde for 30 min.…”
Section: Methodsmentioning
confidence: 99%